A história dirigida : censura e filmes históricos no cinema brasileiro no pós AI-5 - Nascimento Neto, Dário Sousa (2021)
The historical film has emerged as a possibility of greater creative freedom, by the Brazilian moviemakers, when we talk about the edition of the Institutional Act n.5 (AI-5), at December 13th in 1968. If before, the historical movies took place as a spontaneous form in the national cinema, with AI-5 the military governments took the historical theme to a privileged place in the movies production, creating new means of resources for film making. Such phenomenon of cultural guidance by the military government is analyzed regarding the different versions of what would become the Brazilian History between these two poles. With the History in Brazilian Movies being used by the political propaganda, the present research takes as objects 5 films from the 1970s: A Guerra dos Pelados (1971, Sylvio Back); Como Era Gostoso o Meu Francês (1971, Nelson Pereira dos Santos); Os Inconfidentes (1972, Joaquim Pedro de Andrade); Xica da Silva (1976, Carlos Diegues) e Anchieta, José do Brasil (1978, Paulo César Saraceni). By the sum of the film sources with the documents produced by the Public Entertainment and censorship department (DCDP), the research aimed to analyze the agreements and divergences among the film representations and the exaltation of the national pride desired by the militaries in the censorship. Thus, the methodology employed is from the historian Pierre Sorlin, who lists three steps that bases the analysis of a film group; the fixation points, the structure of the films and the relation systems. The fixation points chosen were the catholic church representations, regarding its hegemonic role in Brazilian History, and the black and native (indigenous) bodies representations, essential in the comprehension of the process by which the country passed through during its history, but very marginalized by the traditional historiography of the period. About the document analysis, the assumptions created by Pierre Sorlin fot the film analysis serves to the research as a guide, but the documents extrapolated such representations, what made possible the research to amplify the goal about the verification of the modus operandi of the censorship, as well as the detours mechanisms activated by the moviemakers to deceive the expression freedom restrictions in military dictatorship times.